2017
DOI: 10.1002/jcb.26034
|View full text |Cite
|
Sign up to set email alerts
|

Oncophosphosignaling Favors a Glycolytic Phenotype in Human Drug Resistant Leukemia

Abstract: In chemoresistant leukemia cells (Lucena-1), the low molecular weight protein tyrosine phosphatase (LMWPTP) is about 20-fold more active than in their susceptible counterpart (K562). We found this phosphatase ensures the activated statuses of Src and Bcr-Abl. Since, phosphorylation and dephosphorylation of proteins represent a key post-translational regulation of several enzymes, we also explored the kinome. We hereby show that LMWPTP superactivation, together with kinome reprogramming, cooperate towards gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…These authors identified six possible substrates, of which four, PKM2, GAPDH, α-enolase, and triose phosphate isomerase, take part in the glycolytic pathway. In contrast to the findings reported by Faria and coworkers, it was observed that the inhibition of LMWPTP leads to an inactivation of PKM2, which causes a decrease in glycolytic flux and increase of GLUT1 and hexokinase 2 [8,9]. PRL-3-It was reported that when colorectal cancer cells (LoVo cell line) overexpress, this phosphatase had an increase of glucose consumption and lactate production in comparison to LoVo cell line wild type.…”
Section: Ptps and Warburg Effectmentioning
confidence: 60%
See 1 more Smart Citation
“…These authors identified six possible substrates, of which four, PKM2, GAPDH, α-enolase, and triose phosphate isomerase, take part in the glycolytic pathway. In contrast to the findings reported by Faria and coworkers, it was observed that the inhibition of LMWPTP leads to an inactivation of PKM2, which causes a decrease in glycolytic flux and increase of GLUT1 and hexokinase 2 [8,9]. PRL-3-It was reported that when colorectal cancer cells (LoVo cell line) overexpress, this phosphatase had an increase of glucose consumption and lactate production in comparison to LoVo cell line wild type.…”
Section: Ptps and Warburg Effectmentioning
confidence: 60%
“…LMWPTP-Our group demonstrated that, in chemoresistant chronic myeloid leukemia cells, the LMWPTP was overactivated and cooperated to Warburg effect. A downregulation of mitochondrial proteins-PDH1, SDHA, and VDAC-was also observed, while GLUT 1 expression and production of lactate were increased [8]. Later on, Lori and colleagues performed a phosphoproteomic analysis of A375 melanoma cells with silenced LMWPTP.…”
Section: Ptps and Warburg Effectmentioning
confidence: 99%
“…This change in glucose metabolism depends on the increased transcription of GLUTs, glycolytic enzymes and oncogenes, and increased demand for mitochondrial metabolism for biosynthetic processes [43]. In this scenario, we found out that leukemia cells displaying the high amount of LMWPTP tend to have a predominance of Warburg effect, due to a down-regulation of mitochondrial proteins: PDH1, SDHA, and VDAC and upregulation of GLUT-1 and lactate dehydrogenase, and in turn, improving lactate production [44]. However, Lori and collaborators (2018) have reported the opposite effect of LMWPTP in melanoma metabolic reprogramming.…”
Section: Lmwptp and Mitochondrial Function-warburg Effectmentioning
confidence: 94%
“…The control (0.0 µM) group was treated with the equivalent amount of DMSO. Cells were incubated for 24 h. Cell viability was analyzed by MTT reduction assay as described before, 15 with some modifications. Briefly, the treatment medium was removed, and the cells were incubated with 100 µl/well of MTT solution (0.5 mg/ml, in an FBS‐free culture medium) for 3 h at 37°C, 85% humidified, and 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%